STRATEGI KOMUNIKASI MENYIKAPI ISU INDONESIA "PECAH" - Manihuruk, Amin Saragih (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
After 65 years of independent Indonesia, revealed the surface of issues, discourse, fears that Indonesia could be broken up into 17 countries in 2015.Prediction split, supported by various indicators such as the political elite of this nation not as a figure of expression often leaders and fighters of the people, between groups I classes are often easy to conflict, there is likely no longer a unifying figure like Sukarno and Suharto first. The split could be prevented by the action plan through dissemination of information toall the nations that contains that if Indonesia did not divide us no good. IndonesianantiÂburst communication strategy should be implemented and one of the main priorities of national development. Â Live five years longer, very short period.